Clinical Outcomes of Patients with Heart failure at the Heart Failure Clinic, Sunpasitthiprasong Hospital - Promwong, Waiyaporn; Meenongwah, Jaroonsree; Veerakul, Sumitar; Plookcharoen, Wilaiwan (Vajira Medical Journal : Journal of Urban Medicine, 2021)
Objective: To study the clinical outcomes of heart failure (HF) patients at the HF clinic, Sunpasitthiprasong Hospital. Method: Descriptive study was applied. Purposive sampling was used to recruit 34 patients with HF. Data was collected from March to August 2020, using a personal data questionnaire, the clinical outcome questionnaire for HF patients included New York Heart Association Functional Class (NYHA FC), Left Ventricular Ejection Fraction (LVEF), hospital re-admission, and re-visited the emergency room, self-care behavior questionnaire, and the quality of life questionnaire. Descriptive statistics was used for data analysis. Results: The majority of the subjects were male (61.8%) and age ranged between 37-92 years old, a mean of 59.2 years old (SD = 13.8). All of them had stage C of HF, the period they were diagnosed with HF ranged from 3 months to 6 years, mean 3 years (SD = 18.4). Duration of clinical heart failure was between 3 months and 6 years, two and a half year (SD = 16.4). Before enrolling in the HF clinic, most of the samples had NYHA FC II-III and LVEF was less than 40 percent. After enrolling in HF clinic, most HF patients had NYHA FC I-II with LVEF more than 40 percent, no re-hospitalized and never revisit emergency room. Overall self-care behavior was at a good level and an average score on quality of life was 86.93 (SD. = 20.5), which was a high level. Conclusion: The HF patients who were cared in the HF clinic had better clinical outcomes. As a result, the rate of re-hospitalization and re-visiting emergency room were decreased, and the quality of life of HF patients were increased.